Ethical Infrastructure and Successful Handling of Workplace Bullying - Einarsen, Kari; Mykletun, Reidar J.; Einarsen, Ståle Valvatna; Skogstad, Anders; Salin, Denise (Nordic Journal of Working Life Studies, 2017)
Antecedents and consequences of workplace bullying are well documented. However, the mea- sures taken against workplace bullying, and the effectiveness of such measures, have received less attention. This study addresses this knowledge gap by exploring the role of ethical infrastructure in perceived successful handling of reported workplace bullying. Ethical infrastructure refers to formal and informal systems that enable ethical behavior and disable unethical behavior in organizations. A survey was sent to HR managers and elected head safety representatives (HSRs) in all Norwegian municipality organizations. Overall, 216 organizations responded (response rate = 50.2 percent). The ethical infrastructure accounted for 39.4% of the variance in perceived suc- cessful handling of workplace bullying. Formal sanctions were the only unique and signi cant contributor to the perceived successful handling of workplace bullying. The results substantiate the argument that organizations’ ethical infrastructure relate to the HR managers and HSRs’ percep- tions regarding their organizations’ handling of workplace bullying.